Irrational use of drugs - Md. Shamsur Rahman; David Matanjun; Urban John Arnold D’souza; Wan Salman Wan Saudi; Fairrul Kadir; Tan Teck Song; Mohd. Hijaz Mohd. Sani (Universiti Malaysia Sabah, 2021)
Irrational use of drugs could be detrimental issues in the practices of healthcare communities. This problem arises either because of the wrong prescription or inappropriate self-medication. Faulty prescribing practices and incorrect self-medication will lead to an ineffective treatment regime. Still, they can also be unsafe as these may exacerbate or prolong the illness and distress the patients. In turn, these will incur unnecessary treatment costs. The most typical issues in the irrational use of drugs are the patient’s lack of information about the medicine and inadequate proper consultation from physicians. Lack of regulation in the appropriate use and supply of drugs by the relevant enforcement agencies could also be the problem in the irrational use of drugs. Ulceration and inflammation due to the irrational use of NSAIDs, antibiotics, and unhealthy lifestyle may contribute to the novel therapeutic strategy challenges. The ability to purchase the drugs without a doctor’s prescription of nonsteroidal anti-inflammatory drugs (NSAIDs) was also the landmark event that became the most widely used medications for the anti-inflammatory, analgesic, and antipyretic effects. Inadequate knowledge from both drug providers and patients may contribute to the most recognized influential factors in the irrational use of drugs in various countries. The recommendation should introduce an appropriate educational intervention that can be designed to promote rational prescribing. Proper regulation on prescription practices by policymakers and physicians could be the way to ensure the standard of rational usage of drugs have compliant with the healthcare communities